2014
DOI: 10.1007/s00404-014-3461-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin risk factors for the development of hypertension in pregnancy

Abstract: The results confirm alterations in the peripheral 5-HT system in pregnancy-induced hypertension. Low platelet 5-HT concentration is a common feature of both PIH and pre-eclampsia. The results did not support the hypothesis that hypertension in pregnancy is a trait associated with polymorphic variants of the HTR2A and SLC6A4 or that they have a role in the predisposition to hypertensive disorders in pregnancy. The further studies are necessary to elucidate the role of 5-HT and genetic factors in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…As the 5-HT 2A receptor is a key regulator of placentation (influencing placental growth and function), it is suggested to play a role in the pathophysiology of pre-eclampsia [293,294], thereby influencing the maternal immune system activity. However, the association between pre-eclampsia and 5-HT 2A receptor function was not supported in another study [295]. Moreover, it is hypothesized that factors including maternal diet and genetics can influence the 5-HT 2A receptor promoter [296].…”
Section: Synergistic Impact On 5-ht-ergic Systems and Fetal Neurodevementioning
confidence: 87%
“…As the 5-HT 2A receptor is a key regulator of placentation (influencing placental growth and function), it is suggested to play a role in the pathophysiology of pre-eclampsia [293,294], thereby influencing the maternal immune system activity. However, the association between pre-eclampsia and 5-HT 2A receptor function was not supported in another study [295]. Moreover, it is hypothesized that factors including maternal diet and genetics can influence the 5-HT 2A receptor promoter [296].…”
Section: Synergistic Impact On 5-ht-ergic Systems and Fetal Neurodevementioning
confidence: 87%
“…Although genetic associations of SERT were not assessed in that study, their findings point to the fact that regardless of the genotype presented by the mother, plasma 5-HT levels did not show a significant value (p < 0.05) in patients with established PE. In another study carried out by Sabolovic et al in Croatia, platelet 5-HT concentrations were analyzed in pregnant women with PE, in patients with gestational hypertension without proteinuria, and in healthy pregnancies without complications (i.e., controls) [45]; their findings showed that compared with controls, there was a low platelet 5-HT level in PE-and pregnancy-induced hypertension, but unlike us, they did not find differences in the proportions of genotypes of 5-HTTLPR (tri-allelic version) between study groups. Actually, we are not aware of any study evaluating the association between the 5-HTTLPR variant of the SLC6A4 gene and PE and reporting that the S/S genotype decreases the probability of PE.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT transport is performed by the 5-HTT, which regulates intracellular (in neurons and platelets) and extracellular (in synaptic cleft and plasma) 5-HT concentrations, namely, 5-HT function [45]. Several genetic variants of the 5-HTT-linked promoter region (5-HTTLPR) have been identified [46].…”
Section: Introductionmentioning
confidence: 99%
“…Among the physiological factors for regulating blood pressure, a neurotransmitter and hormone serotonin (5hydroxytryptamine, 5-HT) were considered. Its precise function in normal or altered blood pressure is unclear, likely because of the complex events of blood 5-HT in vitro [10,11]. The association of serotonin and development of hypertension was investigated by the blood platelets, which served as a primary storage location, and were easily accessible source of serotonin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Its precise function in normal or altered blood pressure is unclear, likely because of the complex events of blood 5-HT in vitro [10,11]. The association of serotonin and development of hypertension was investigated by the blood platelets, which served as a primary storage location, and were easily accessible source of serotonin [10]. Blood platelet serotonin 2A receptor (HTR2A, also known as 5-HTR2A), regulates platelet activation and serotonin release; whereas 5-HTR2A located in vascular smooth muscle, endothelial cells, and cardiomyocytes regulate blood pressure and heart rate [12].…”
Section: Introductionmentioning
confidence: 99%